2016
DOI: 10.3109/13880209.2016.1150306
|View full text |Cite
|
Sign up to set email alerts
|

Metformin pretreatment enhanced learning and memory in cerebral forebrain ischaemia: the role of the AMPK/BDNF/P70SK signalling pathway

Abstract: Context Metformin induced AMP-activated protein kinase (AMPK) and protected neurons in cerebral ischaemia. Objective This study examined pretreatment with metformin and activation of AMPK in molecular and behavioral levels associated with memory. Materials and methods Rats were pretreated with metformin (200 mg/kg) for 2 weeks and 4-vessels occlusion global cerebral ischaemia was induced. Three days after ischaemia, memory improvement was done by passive avoidance task and neurological scores were evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…However, metformin successfully acted as a protective drug in various disease models when used to pretreat animals prior to the induction of diseases, including acute kidney injury 44 and cerebral forebrain ischemia. 45,46 Thus, it is possible that metformin is more beneficial if it is given at an earlier, prediabetic stage as a “preventive” strategy rather than as a “treatment” for diabetic retinas.…”
Section: Discussionmentioning
confidence: 99%
“…However, metformin successfully acted as a protective drug in various disease models when used to pretreat animals prior to the induction of diseases, including acute kidney injury 44 and cerebral forebrain ischemia. 45,46 Thus, it is possible that metformin is more beneficial if it is given at an earlier, prediabetic stage as a “preventive” strategy rather than as a “treatment” for diabetic retinas.…”
Section: Discussionmentioning
confidence: 99%
“…Skim milk 5% was used to block the membrane (overnight exposure), and HRP‐conjugated IgG rabbit polyclonal anti‐mouse secondary antibody was applied to labeled proteins during 1 hour of shacking (dilution 1: 2000; Abcam, USA). Using an Electrochemiluminescence kit (ECL), protein bands appeared in Bio‐Rad Gel Doc system and analyzed with IMAGE J software in the last step of the Western blot procedure …”
Section: Methodsmentioning
confidence: 99%
“…Consistently, previous reports have shown that Met could elevate the BDNF level. Pretreatment of rats with Met for 2 weeks improved the neurological scores and BDNF level in global cerebral ischemia . In a recent study, the antioxidant and antisenescence effects of Met were investigated in mouse olfactory ensheathing cells.…”
Section: Discussionmentioning
confidence: 99%